A Case Study of Holomorphic Semigroups - Subedi, Bishnu Hari; Singh, Ajaya (Journal of Nepal Mathematical Society, 2020)
In this paper, we investigate some characteristic features of holomorphic semigroups. In particular, we investigate nice examples of holomorphic semigroups whose every left or right ideal includes minimal ideal. These examples are compact topological holomorphic semigroups.